2011
DOI: 10.1103/physrevb.83.134437
|View full text |Cite
|
Sign up to set email alerts
|

Use of Stevens coefficients for the prediction of magnetic transitions in pseudobinaryR1xRx'Al

Abstract: Recent heat capacity and low field magnetic susceptibility measurements revealed unusual magnetic phenomena occurring in Er 1-x R x Al 2 systems (where R = Dy, Tb) in the vicinity of a "magic" concentration of x = 0.25. Empirically, the reasons for such behavior were attributed to different shapes of the 4f charge densities of the R 3+ ions, which are represented by the opposite signs of the second order Stevens' factors. Here we show that by using both the signs and magnitudes of the second order Stevens' fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
(24 reference statements)
1
10
0
Order By: Relevance
“…Mixing one lanthanide (R) with another (R') in pseudobinary compounds such as Er 1-x Dy x , Er 1-x Dy x Al 2 , Er 1-x Tb x Al 2 , and Tm 1-x Tb x Al 2 [8,9,10,11] results in unusual low temperature anomalies in heat capacity and multiple ordering phenomena. In some cases, additional first order transitions are observed below the main FM-PM transition at T C .…”
mentioning
confidence: 99%
“…Mixing one lanthanide (R) with another (R') in pseudobinary compounds such as Er 1-x Dy x , Er 1-x Dy x Al 2 , Er 1-x Tb x Al 2 , and Tm 1-x Tb x Al 2 [8,9,10,11] results in unusual low temperature anomalies in heat capacity and multiple ordering phenomena. In some cases, additional first order transitions are observed below the main FM-PM transition at T C .…”
mentioning
confidence: 99%
“…This approach has been successfully applied for rare earth-based magnetic systems, we refer readers to some of our recent publications. 47,48,49,50,51,52,53,54,55,56 Our low temperature XRD experimental results indicate that DyFe 4 Ge 2 undergoes a transformation from the high temperature paramagnetic (PM) tetragonal (P4 2 /mnm) to the low temperature antiferromagnetic (AFM) orthorhombic (Cmmm) structure at ~60 K.…”
Section: Theoretical Investigationsmentioning
confidence: 72%
“…The crystal structure, lattice parameters, phase concentrations were determined by performing Rietveld refinement using LHPM-RIETICA. 45 Single The starting atomic parameters derived via direct methods and the program SIR 97 48 were subsequently refined using the program SHELX-97 49 (full-matrix least-squares on F 2 ) with anisotropic atomic displacement parameters included for all atoms.…”
Section: Methodsmentioning
confidence: 99%
“…2 Recent studies showed that when two lanthanides with 4f electron charge densities of different shape are mixed together in pseudo-binary R 1-x R' x Al 2 compounds (R and R' are lanthanide metals where R has a positive second order Stevens' factor and the same for R' is negative ), interesting magnetic phenomena are observed. 3,4,5,6,7 For certain critical concentrations centered at x = 0.25, sharp peaks, representing first order phase transitions, are observed in the heat capacity, C P , data of the R 1-x R' x Al 2 alloys. The peaks are suppressed upon the application of weak magnetic fields.…”
Section: Introductionmentioning
confidence: 99%